RELEVANSI PENDIDIKAN BAHASA INDONESIA DI SMP DENGAN PENDIDIKAN PAULO FREIRE - Desi Ratna Ayu; Sunarya, Yaya (IKIP Siliwangi, 2024)
Paulo Freire's education is very important for today's education, so it would be very good if it were applied in today's education. In the world of education, Indonesian language education is very important to increase students' creativity and activeness, especially in junior high school, because this is the golden age where students' creativity and activeness begins. To find out this, further studies are needed regarding the relevance of Paulo Freire's education and Indonesian language education in junior high schools. This research uses the methodliterature review with a qualitative descriptive presentation. Sources of research data come from journal articles, books and other sources. Data collection is in the form of literary data using listening, reading and note-taking techniques. Data analysis techniques using content analysis techniques.The results of research based on objectives, methods, concepts, student positions and educators' positions show that Indonesian language education in junior high schools is related to Paulo Freire's education. In other words, Indonesian language education in junior high school uses liberation as an important part of educational activities. This educational liberation is expected to provide maximum results for students to achieve learning goals.